Flexspline tooth fault detection in harmonic drives using instantaneous angular speed signal energy-difference weighting - Haipeng Wang; Yu Guo; Xinchao Yin; Xin Chen; Zhile Wang (Structural Health Monitoring, 2026)
Harmonic drives are widely used in industrial robots. However, due to the flexspline’s high contact ratio and the elastic deformation, conventional signal processing, such as synchronous averaging, struggle to extract information about flexspline tooth faults. To address this issue, this article proposes an instantaneous angular speed (IAS) signal energy-difference weighting (EDW) method for flexspline fault detection. First, the IAS signal is calculated by the outputs from the built-in encoder, and synchronous averaging is performed to reduce aperiodic components by using the full repeating cycle of the flexspline relative motion as the reference. Second, the energy difference weighting matrix is created using two angular positions separated by one quarter of the input cycle, with higher weights as signed to locations with greater energy variation. Third, a polar energy spectrum in the angular domain is introduced to depict the angular waveform and its energy distribution. The energy map is compared to the installation orientation of the defective flexspline, and the IAS signal’s crest factor (CF) is compared before and after EDW processing. These results support the use of the proposed method to detect flexspline tooth breakage and provide an interpretable representation.